Demographics, Clinical Features, Laboratory Results Characteristic of COVID-19 Patients at Dr. Wahidin Sudirohusodo Hospital - Lolongan, Calvarica Lun; Esa, Tenri; Bahrun, Uleng (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Coronavirus Disease 2019 (COVID-19) has spread throughout the world since 2020. WHO declared COVID-19 as a pandemic. Pandemic status has now ended, but the rapid spread of COVID-19 can be a concern to anticipate a new spike. Various studies and results regarding characteristics of COVID-19 patients such as age, gender, clinical symptoms, and laboratory examination results have been carried out to provide an overview of various factors that can support COVID-19 infection. Based on this, authors are interested in identifying characteristics of COVID-19 patients based on age, gender, origin, education, occupation, dominant symptoms, severity, COVID-19 biomarkers (NLR, CRP, procalcitonin, D-dimer, ferritin), and CT value at Dr. Wahidin Sudirohusodo Hospital as COVID-19 referral center in Eastern Indonesia. This study aimed to determine the characteristics of COVID-19 patients at Dr. Wahidin Sudirohusodo Hospital, Makassar. A descriptive cross-sectional study on 650 COVID-19 patients was performed at Dr. Wahidin Sudirohusodo Hospital, from January 2020–July 2022. The data were described based on age, gender, regional origin, education, occupation, severity (asymptomatic, mild, moderate, severe, and critical), dominant symptoms, laboratory biomarker (NLR, CRP, procalcitonin, D-dimer, ferritin) and CT value. There were more males than females (52.8% vs. 47.2%), age range 26-35 years (20.3%), from South Sulawesi (91.3%), non-PNS (37.1%), and senior high school education was the largest (29.2%). Dominant symptoms were respiratory distress (26.9%) and mild severity (41.7%). Based on the results of COVID-19 biomarker research, it is known that the range of COVID-19 biomarkers differs between mild and critical degrees. In mild degrees, the range of COVID-19 biomarkers is lower than critical degrees. It is known that the range of each biomarker in mild degree NLR 1.02-7.14, CRP 0.20-35.20 mg/l, procalcitonin 0.05-0.75 ng/mL, D-dimer 0.11-1.04 µg/mL, and ferritin 16.15-402,40 ng/mL. Higher COVID-19 susceptibility among males and certain occupational groups. Symptoms vary widely, with some cases showing no symptoms. Disease severity ranges from mild to asymptomatic, with biomarkers indicating progression.